Decacyclene Radical Anions Showing Strong Low‐energy Intramolecular Absorption and Magnetic Coupling of Spins in a Hexagonal Network. Issue 17 (22nd July 2020) - Konarev, Dmitri V.; Kuzmin, Aleksey V.; Khasanov, Salavat S.; Shestakov, Alexander F.; Otsuka, Akihiro; Yamochi, Hideki; Kitagawa, Hiroshi; Lyubovskaya, Rimma N.
Abstract: Two salts of the aromatic hydrocarbon decacyclene, cryptand[2.2.2](Cs + ) (decacyclene .− ) (1 ) and Bu3 MeP + (decacyclene .− ) (2 ), were obtained. In both salts, decacyclene .− radical anions formed channels occupied by cations. However, corrugated hexagonal decacyclene .− layers could be outlined in the crystal structure of 1 with several side‐by‐side C⋅⋅⋅C approaches. The decacyclene .− radical anions showed strong distortion in both salts, deviating from the C 3 symmetry owing to the repulsion of closely arranged hydrogen atoms and the Jahn‐Teller effect. Radical anions showed intense unusually low energy absorption in the IR‐range, with maxima at 4800 and 6000 cm −1 . According to the carculations, these bands can originate from the SOMO‐LUMO+1 and SOMO‐LUMO+2 transitions, respectively. Radical anions exhibited a S =1/2 spin state, with an effective magnetic moment of 1.72 μB at 300 K. The decacyclene .− spin antiferromagnetically coupled with a Weiss temperature of −11 K. Spin ordering was not observed down to 1.9 K owing to spin frustration in the hexagonal decacyclene .− layers. Abstract : New method for the preparation of aromatic hydrocarbon salts has been developed, providing cryptand[2.2.2](Cs + )(decacyclene .− ) (1 ) and Bu3 MeP + (decacyclene .− ) (2 ) salts. Salt 1 showed strong NIR absorption in decacyclene .− at 4000–6000 cm −1, respectively, and essential magnetic coupling of spins in hexagonal hydrocarbon layers.